Tongue-in-Groove Technique for Rhinoplasty: Technical Refinements and Considerations - Spataro, Emily A.; Most, Sam P. (Facial Plastic Surgery, 2018)
A key concept in successful rhinoplasty surgery is maintaining or increasing tip support, and addressing tip projection and rotation. The tongue-in-groove (TIG) technique is a method to achieve this goal using sutures to create a strong connection between the septum and medial crura to change tip rotation and projection. Criticisms of this method include that it may cause stiffness of the nasal tip and columellar retraction. TIG is routinely used by the authors during anterior septal reconstructions (a modified extracorporeal septoplasty technique), as well as in primary and revision aesthetic and functional rhinoplasties. Through this review, technical aspects of the TIG technique are discussed, as well as how pitfalls of the technique can be avoided, as illustrated by several rhinoplasty patient examples.
Keywords: rhinoplasty; tongue-in-groove; nasal tip; tip projection; tip rotation